2022
DOI: 10.1063/5.0087073
|View full text |Cite
|
Sign up to set email alerts
|

The stability of expanding reactive shocks in a van der Waals fluid

Abstract: Despite the extensive literature accumulated since the pioneering works of D'yakov and Kontorovich in the 1950s, the stability of steady shocks is still an open question when realistic boundary conditions are accounted. The consideration of a supporting mechanism, which is indeed a necessary condition for shock steadiness, modifies the perturbation shock dynamics in the unstable range. The Noh problem is a suitable example to form steady expanding shocks. This configuration is of great interest to the high-ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 86 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…It is found that the initial value problem associated with the corrugated planar-geometry case is qualitatively different from that corresponding to cylindrical and spherical steady expanding shocks associated with the Noh problem, addressed in Velikovich et al (2016), Huete et al (2021) andCalvo-Rivera et al (2022). It was demonstrated there that the shock exhibits an unstable power-law evolution when h > h c and the perturbation mode number is sufficiently high.…”
Section: Forced Resonance In the Sae Regimementioning
confidence: 84%
See 3 more Smart Citations
“…It is found that the initial value problem associated with the corrugated planar-geometry case is qualitatively different from that corresponding to cylindrical and spherical steady expanding shocks associated with the Noh problem, addressed in Velikovich et al (2016), Huete et al (2021) andCalvo-Rivera et al (2022). It was demonstrated there that the shock exhibits an unstable power-law evolution when h > h c and the perturbation mode number is sufficiently high.…”
Section: Forced Resonance In the Sae Regimementioning
confidence: 84%
“…(2021) and Calvo-Rivera et al. (2022). It was demonstrated there that the shock exhibits an unstable power-law evolution when and the perturbation mode number is sufficiently high.…”
Section: Forced Resonance In the Sae Regimementioning
confidence: 96%
See 2 more Smart Citations
“…Pandey [27], and Hermet et al [28], studied the propagation of shock waves with and without including the overtaking disturbances on the downstream flow inside a cross-sectional tube or channel for different gases. Recently, A. Calvo-Rivera et al [29], analyzed in detail the stability of a steadily expanding shock-front and its application to a reactive shock using Rankine-Hugoniot equations in a van der Waals gas. Further, Rivera and Huete [30] revisited the MHD shockfront stability using ideal gas equation of state (EoS), van der Waals EoS and also for some metals such as aluminum.…”
Section: Introductionmentioning
confidence: 99%